2000
DOI: 10.1007/s004210000254
|View full text |Cite
|
Sign up to set email alerts
|

Glucose uptake by individual skeletal muscles during running using whole-body positron emission tomography

Abstract: The purpose of this study was to examine, by positron emission tomography (PET), the distribution of [18F]fluoro-deoxy-glucose ([18F]FDG) uptake by human muscles during 35 min of running. Thirteen healthy male subjects were studied, seven of whom participated in the exercise study. Running intensity was kept constant such that the subjects' heart rates were maintained at between 140 and 150 beats per minute. [18F]FDG [62.9 (14.8) MBq, mean (SD)] was injected after 15 min of running. PET imaging was started imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 0 publications
3
43
0
2
Order By: Relevance
“…The anterior compartment includes the tibialis anterior and toe extensor muscles. These muscles are active during walking and running (13,15,16) because they decelerate the movement of the foot to the ground after initial heel contact, and they also function concentrically to bring the foot into dorsiflexion during the swing phase of gait. Because all subjects ambulated independently into the clinic for their PET/CT scans, anterior compartment muscle activity occurred in all subjects immediately before the scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior compartment includes the tibialis anterior and toe extensor muscles. These muscles are active during walking and running (13,15,16) because they decelerate the movement of the foot to the ground after initial heel contact, and they also function concentrically to bring the foot into dorsiflexion during the swing phase of gait. Because all subjects ambulated independently into the clinic for their PET/CT scans, anterior compartment muscle activity occurred in all subjects immediately before the scans.…”
Section: Discussionmentioning
confidence: 99%
“…No prospective study on the physiologic uptake of 18 F-FDG in healthy subjects has been published. 18 F-FDG PET was used to examine metabolic muscle activity in healthy subjects during running (13)(14)(15), walking (16), and bicycle exercise (17,18). These studies showed that PET can be useful as an alternative technique for evaluating muscle activity on the basis of muscle glucose uptake.…”
mentioning
confidence: 99%
“…While some studies have used PET-FDG for assessing muscular dystrophyrelated cardiomyopathy in patients 21 , it has yet to be assessed in significant studies of skeletal muscle metabolism in DMD patients. There is strong evidence, however, that PET-FDG will be a useful tool for monitoring degeneration in DMD patients since it is a direct indicator of skeletal muscle glucose metabolism [22][23][24][25][26][27] . Areas of myofibre necrosis and subsequent fibrosis can be detected since fibrotic tissue is not metabolically active and thus should not accumulate 18 F-FDG 21 .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Previous studies of glucose metabolic imaging of skeletal muscle by [ 18 F]FDG PET are categorized into three topics: 1) glucose metabolic imaging during exercise (Fujimoto, et al, 1996, Fujimoto, et al, 2000, Iemitsu, et al, 2000, Kemppainen, et al, 2002, Oi, et al, 2003, Shinozaki, et al, 2003, Tashiro, et al, 1999, 2) comparison between trained and untrained individuals , Takala, et al, 1999, and 3) intramuscular metabolic heterogeneity in exercising muscle (Pappas, et al, 2001 …”
Section: F]fdg Petmentioning
confidence: 99%
“…To map glucose metabolism and muscle activity, walking (Oi, et al, 2003), running (Fujimoto, et al, 1996, Fujimoto, et al, 2000, Iemitsu, et al, 2000, Oi, et al, 2003, Tashiro, et al, 1999, cycling (Kemppainen, et al, 2002), and shoulder muscle exercise (Shinozaki, et al, 2003) was used in previous studies. Much interesting evidence was gained from these studies.…”
Section: F]fdg Petmentioning
confidence: 99%